Costovertebral joint involvement in radiographic axial spondyloarthritis: A case‐series computed tomography study. (18th January 2023) - Shouval, Aniela; Croitoru, Simona; Keret, Shiri; Eshed, Iris; Slobodin, Gleb
Abstract: Aims: To evaluate structural changes of costovertebral joints (CVJ) in patients with radiographic axial spondyloarthritis (rAxSpA) using computed tomography (CT) studies. Methods: Available chest or thoracic spine CT studies of 17 patients with rAxSpA and 17 patients with rheumatoid arthritis (RA) were analyzed. Ankylosis, erosions, joint space narrowing, and osteophytes were assessed. Results: The groups were similar by patients' average age, but the rAxSpA group included more males (11/17) compared to the RA group (4/17, p  = 0.036). In all, 748 CVJ were assessed in each patient group, including 408 head‐vertebral joints (HVJ) and 340 costotransverse joints (CTJ). rAxSpA patients had significantly more total CVJ lesions ( p  < 0.001 for all comparisons), more lesions in the HVJ ( p  < 0.001, for all comparisons), and more lesions in the CTJ ( p  ≤ 0.005, for all comparisons, except for osteophytes), compared to the RA group. All types of lesions, including ankylosis, erosions, narrowing, and osteophytes, were seen more frequently in rAxSpA patients. Joint space narrowing and ankylosis of the CVJ were the most frequently seen findings in rAxSpA and were distributed throughout the thoracic spine. Conclusions: Structural pathology of the CVJ was more commonly observed in patients with rAxSpA than in RA patients in this study.